The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/md.0000000000028438
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of greater occipital nerve block for pain relief in patients with postdural puncture headache

Abstract: Background: This study aimed at assessing the therapeutic effectiveness of greater occipital nerve block (GONB) against postdural puncture headache (PDPH). Methods: Studies investigating analgesic effects of GONB against PDPH in adults were retrieved from the MEDLINE, EMBASE, Google scholar, and Cochrane central databases from their inception dates to May, 2021. Pain score at postprocedural 24 hours was the primary endpoint, while secondary endpoints were pain score at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…There are recent studies, however, that suggest sphenopalatine ganglion block may also be an effective, less invasive successful treatment modality (161,162,167). Additionally, occipital nerve blocks have been used successfully in postdural headaches in patients with symptoms refractory to other treatments (168,169). Both sphenopalatine ganglion block and occipital nerve blocks are supported by case reports, but there is currently insufficient evidence to recommend either sphenopalatine ganglion or occipital nerve blocks as the primary treatment of obstetric PDP headache (170).…”
Section: Secondary Headachesmentioning
confidence: 99%
“…There are recent studies, however, that suggest sphenopalatine ganglion block may also be an effective, less invasive successful treatment modality (161,162,167). Additionally, occipital nerve blocks have been used successfully in postdural headaches in patients with symptoms refractory to other treatments (168,169). Both sphenopalatine ganglion block and occipital nerve blocks are supported by case reports, but there is currently insufficient evidence to recommend either sphenopalatine ganglion or occipital nerve blocks as the primary treatment of obstetric PDP headache (170).…”
Section: Secondary Headachesmentioning
confidence: 99%
“…Seventh, fibrin glue should be reserved for management of PDPH refractory to EBP or when autologous blood injection is contraindicated (evidence grade: I; level of certainty: low). Important supporting references were Russell et al, Melchart et al, Sluder, Giaccari et al, and Chang et al…”
Section: Resultsmentioning
confidence: 95%
“…Fourth, regular multimodal analgesia, including acetaminophen and nonsteroidal antiinflammatory drugs, should be offered to all patients with PDPH unless contraindicated 41 8 Melchart et al, 43 Sluder, 44 Giaccari et al, 45 and Chang et al 46 Question 7: Is Imaging Required in PDPH Management?…”
Section: Moderatementioning
confidence: 99%
“…A 2021 meta-analysis examining GON blocks for the treatment of PDPH found that it reduces pain scores for 24 h and may obviate the need for EBP. However, they were only able to find four RCTs to include in their analysis, and there was a high heterogenicity of the data [68]. At this time, it is not possible to definitively state that GON blocks are effective at managing PDPH without further trials and more data.…”
Section: Peripheral Nerve Blockadementioning
confidence: 99%